2017
DOI: 10.1007/s10620-017-4739-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Antivirals Decreased Tumor Recurrence After Initial Treatment of Hepatitis C Virus-Related Hepatocellular Carcinoma

Abstract: DAA therapy significantly decreased recurrence rate when it was performed after initial HCC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 23 publications
5
101
0
5
Order By: Relevance
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Direct‐acting antivirals (DAAs) have been considered to represent a long‐awaited solution in the treatment of hepatitis C. Thus, recent reports of the increased incidence of recurrent and de novo hepatocellular carcinoma (HCC) after DAA use have raised great concern. Following the publication of these reports, several other studies have confirmed the increased occurrence of HCC after DAA use, whereas others have refuted these findings . In a recent meta‐analysis of 41 DAA‐ and interferon (IFN)‐based studies (26 of HCC occurrence and 17 of HCC recurrence) including a total of 13,875 patients (90% with liver cirrhosis [LC]), DAA therapy was not associated with increased HCC occurrence or recurrence .…”
mentioning
confidence: 99%
“…use, (3,4) whereas others have refuted these findings. (5)(6)(7) In a recent meta-analysis of 41 DAA-and interferon (IFN)-based studies (26 of HCC occurrence and 17 of HCC recurrence) including a total of 13,875 patients (90% with liver cirrhosis [LC]), DAA therapy was not associated with increased HCC occurrence or recurrence. (8) In general, these studies show that the rate of recurrence is more variable than that of de novo HCC.…”
mentioning
confidence: 99%
“…In Japan report, the recurrence rate increased in accordance with treatment times in the past [11]. One-year recurrence rates were 18.1, 28.2, and 60.2%, and 2-year rates were 22.…”
Section: Hcc Recurrence After Daa Treatmentmentioning
confidence: 87%